Leader-Member Exchange Terhadap Kepuasan Kerja: Mediasi Komitmen Organisasi dan Perceived Organizational Support - Sharifah Fathia Hannisa Noor; Jufrizen Jufrizen (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose − This study examines and analyses the effect of Leader-Member Exchange on job satisfaction through organizational commitment and perceptions of organizational support at the North Sumatra BKKBN Office directly and indirectly.Methodology − The approach used in this study is an associative quantitative approach. The population in this study were all employees at the North Sumatra BKKBN Office. The sample in this study used the saturated sample method, totalling 91 employees at the North Sumatra BKKBN Office. Data collection techniques in this study used interviews and questionnaires. Data analysis techniques in this study used a quantitative approach using SEM_PLS.Findings − The results of this study indicate that Leader-Member Exchange, organizational commitment and Perceived organization support have a positive and significant effect on job satisfaction, Leader-Member Exchange, have a positive and significant effect on organizational commitment and perceived organization support, Leader-Member Exchange has a positive and significant effect on job satisfaction through Organizational Commitment and Perceived Organizational Support at the North Sumatra BKKBN Office.Originality/Novelty − This study examines LMX as a more comprehensive predictor of job satisfaction and then explicitly explores the importance of organizational commitment and perceived support as mediators in the relationship between LMX and job satisfaction.Implications −This research has shown that organizational commitment and perceived organizational support mediate the effect of Leader-Member Exchange on job satisfaction through organizational commitment. The recommendation for further research is to analyze or use the variable perceived organization support as an independent variable, not as a mediating variable